The Irish Dail Election 2007 - SUITER, JANE (Irish Political Studies, 2007)
The Irish Republic Dail election held on 24 May 2007 was considered to be the most exciting in a generation or more. The early part of the campaign was dominated by questions relating to Taoiseach Bertie Ahern?s personal finances and the result of the election was wide open until the last days of the campaign. With hindsight the election was also significant for a number of other reasons. First, it marked the occasion when a Taoiseach was returned to power for the third time in a row, emulating the achievement of Eamonn De Valera and cementing Flanna Fail?s position as the dominant party of power. Second, it was the first occasion of the Green party entering government. Third, Fine Gael had a remarkably good election and as a result the smaller parties failed to make anticipated gains, returning the Dail to what looks suspiciously like the old two-and-a-half party system.
PUBLISHED
Keywords: Ireland; election; Elections